THE EFFECT OF BLENDED LEARNING MODEL TO INCREASE BIOLOGY LEARNING OUTCOMES OF STUDENTS OF CLASS XI IPA SMA NEGERI 5 LANGSA - Siregar, Nira Pradina; Sarjani, Tri Mustika; Sofian, Sofian (Jurnal Biologi Sains dan Kependidikan, 2021)
The problem that often occurs in learning is the low student learning outcomes. The results of observations at the beginning of the even semester of the 2021 academic year implementation of learning at SMA Negeri 5 Langsa using offline learning with limited learning time caused students to have very little time to interact with teachers. The purpose of this study was to determine whether there was an effect and how much influence the blended learning model had on improving biology learning outcomes for students of class XI science at SMA Negeri 5 Langsa. The research method is an experimental method, with a quantitative approach. The research design used in this study is a Quasi Experimental Design Nonequivalent Control Group Design. The conclusion of this study is that there is an effect of the blended learning model to significantly improve the biology learning outcomes of class XI science students at SMA Negeri 5 Langsa. The effect of the blended learning model to improve biology learning outcomes for students of class XI IPA SMA Negeri 5 Langsa, namely after being given treatment with the blended learning model in class XI IPA 2, the effect of learning outcomes increased with a large effect of 25.74. Suggestions that the author can convey to teachers are to use blended learning models that can be used as an option to improve student learning outcomes.Keywords: Influence, blended learning model, learning outc